A study of the comprehension skills and strategies of ABE students - Lori A. Forlizzi (Adult Education Research Conference, 1993)
This research revealed that ABE students are surprisingly good monitors of their reading comprehension. However, areas for improvement exist, especially regarding knowledge of variables and strategies that influence reading.